HUBUNGAN POWER OTOT TUNGKAI DAN BERAT BADAN TERHADAP HASIL KEMAMPUAN LOMPAT JAUH PADA ATLET LOMPAT JAUH PELATDA MAYUNG TAHUN 2017 - Lubis, Muhammad Ridwan; Isyani, Isyani (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2019)
There is lack motivation on the long jump athletes of PELATDA which cannot be separated from the understanding in coaching on the athletes. Coaching is an effort to improve the performance. This study aims to determine the correlation between limb muscle power and body weight on the long jump ability of PELATDA athletes Mayung in 2017. This research is a correlation research. This study uses three variables consisting of two independent variables (limb muscle power and body weight) and one dependent variable- the long jump ability. The population used in this study is all long jump athletes of PELATDA Mayung as many as 7 athletes. The data analysis uses the technique of study population and total sampling is 7 athletes. This research uses multiple correlation analysis at 5% significant level. The results of this study shows that (1) there is a significant correlation between limb muscle power variables on the long jump ability of PELATDA athletes Mayung in 2017, that is 0.941 (2) There is a significant correlation between the body weight variables on the long jump abiity of PELATDA athletes Mayung in 2017, that is 0.869 (3) there is a significant correlation between variables of limb muscle power and body weight on the long jump ability of PELATDA athletes Mayung in 2017, that is 0.854.